Strategic enhancement of motor vehicle taxation in Jambi Province: A pathway to strengthened regional fiscal autonomy - Zamzami, Zamzami; Dahmiri, Dahmiri; Parkhurst, Helen (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
This research aims to develop strategies for boosting motor vehicle tax revenue in Jambi Province. It employs a combination of secondary and primary data, including a time series analysis from 2007 to 2021. The data covers the number of vehicles, the average motor vehicle tax, and revenue realization in Jambi Province. Primary data were gathered from in-depth interviews with experts in local taxation. The study employs descriptive analysis and a SWOT approach for analytical depth. Findings reveal a consistent increase in two- and four-wheeled vehicles from 2017 to 2021 in Jambi Province, potentially signalling economic growth or shifts in mobility patterns. A critical insight from this study is the notable disparity between the rising number of vehicles and the corresponding realization of tax revenue. Specifically, the average tax revenue realization for two-wheeled vehicles during this period was just 25.03 per cent, and for four-wheeled vehicles, approximately 62.30 per cent. The study highlights the crucial role of enhancing Original Regional Revenue (PAD) through motor vehicle taxes as a key strategy to lessen dependence on central funding. It suggests implementing public education initiatives, enhancing public transportation service quality, and reinforcing taxpayer compliance as effective strategies to achieve this goal.